Sociology of gender and public sphere in the Algerian society - arzazi, mohamed (Journal of Social Sciences and Humanities, 2021)
Woman occupied a position of inferiority within the public sphere where her presence constituted some threat towards the masculine society and against his social privileges. The organization of the public sphere based on gender as social and cultural data are therefore a necessity. Indeed, the public sphere became a sphere with masculine domination where the inferiority of the woman watches each other at different levels and where this one is the victim of different types of marginalization and inferiority and the target of material and symbolic resistance. In line with this problem, this contribution represents a field investigation to a population of Tlemcen town; the central objective is to try to understand the relationship between gender and public sphere, and especially the position woman within this sphere. On methodological plan, our research uses semi-directive interview and leans principally on a qualitative approach.